Lattice Boltzmann Simulation of Particle Motion in Binary Immiscible Fluids (Communications in Computational Physics, 2018)
We combine the Shan-Chen multicomponent lattice Boltzmann model andthe link-based bounce-back particle suspension model to simulate particle motion inbinary immiscible fluids. The impact of the slightly mixing nature of the Shan-Chenmodel and the fluid density variations near the solid surface caused by the fluid-solidinteraction, on the particle motion in binary fluids is comprehensively studied. Oursimulations show that existing models suffer significant fluid mass drift as the particlemoves across nodes, and the obtained particle trajectories deviate away from thecorrect ones. A modified wetting model is then proposed to reduce the non-physicaleffects, and its effectiveness is validated by comparison with existing wetting models.Furthermore, the first-order refill method for the newly created lattice node combinedwith the new wetting model significantly improves mass conservation and accuracy.